The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1111/cpr.12349
|View full text |Cite
|
Sign up to set email alerts
|

LINC00152: A pivotal oncogenic long non‐coding RNA in human cancers

Abstract: In recent years, increasing evidence has shown the potential role of long non-coding RNAs (lncRNAs) in multiple cancers. Deregulation of lncRNAs was detected being closely associated with many kinds of tumours where they can act as a tumour suppressor or accelerator. LINC00152 was identified as an oncogene involved in many kinds of cancers, such as gastric cancer, hepatocellular carcinoma, colon cancer, gallbladdercancerandrenalcellcarcinoma.Moreover,inhibitionofLINC00152cansup-press proliferation, migration a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
71
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(74 citation statements)
references
References 55 publications
(73 reference statements)
3
71
0
Order By: Relevance
“…[29] Recent studies have shown that LINC00152 is highly expressed in a variety of tumors, such as, glioma, [30] nonsmall cell lung cancer, [31] gastric cancer, [32] etc. [29] Recent studies have shown that LINC00152 is highly expressed in a variety of tumors, such as, glioma, [30] nonsmall cell lung cancer, [31] gastric cancer, [32] etc.…”
Section: Discussionmentioning
confidence: 99%
“…[29] Recent studies have shown that LINC00152 is highly expressed in a variety of tumors, such as, glioma, [30] nonsmall cell lung cancer, [31] gastric cancer, [32] etc. [29] Recent studies have shown that LINC00152 is highly expressed in a variety of tumors, such as, glioma, [30] nonsmall cell lung cancer, [31] gastric cancer, [32] etc.…”
Section: Discussionmentioning
confidence: 99%
“…LncRNAs have emerged as possible biological regulators of a wide range of cellular activities such as proliferation, apoptosis, migration, and invasion [19]. Over the past several years, emerging data showed that alterations in the expression of lncRNAs contribute to the pathogenesis of many human cancers, where they function as either oncogenes or tumor suppressors [20].…”
Section: Discussionmentioning
confidence: 99%
“…ncRNAs are essential for the regulation and execution of key cellular processes, including proliferation, apoptosis, autophagy, differentiation, metabolism, migration, differentiation and invasion . It therefore comes as no surprise that ncRNAs are deregulated in most, if not all, kinds of diseases, including neoplastic, inflammatory and metabolic diseases . From a clinical perspective, the frequent alteration of ncRNA abundance in the body fluid, such as saliva, blood and urine, during diseases make this class of molecules promising candidates for development into biomarkers for early diagnosis and prognostication …”
Section: Introductionmentioning
confidence: 99%